Oceanographic Data of the 35th Japanese Antarctic Research Expedition from November 1993 to March 1994 - オカノ, ヒロフミ; オガワ, アキヒコ; OKANO, Hirofumi; OGAWA, Akihiko (National Institute of Polar Research, 1998)
P(論文) The results of oceanographic observations on the icebreaker "Shirase" and tidal observations at Syowa Station, Antarctica, are presented in this report. The oceanographic observations were carried out in the summer mission of the 35th Japanese Antarctic Research Expedition (JARE-35) from November 1993 to March 1994. The tidal observation was continued through the winter mission of JARE-34 from February 1992 to January 1993. departmental bulletin paper